A novel method to dry age beef by using vacuum packaging - M.L. Ahnström; M. Seyfert; Melvin C. Hunt; D.E. Johnson (Kansas Agricultural Experiment Station Research Reports, 2006)
The traditional dry-aging method for beef was compared with a novel technique of dry aging in a highly moisture-permeable vacuum bag. Paired beef strip loins were cut into four sections and were dry aged traditionally (unpackaged) or packaged in the novel bag for 14 or 21 days. Cooking loss, tenderness, juiciness, and all flavor attributes were similar for the aging methods. Beef dry aged in the bag had less weight loss during aging, less trim loss after 21 days, and lower yeast counts after either aging time, compared with beef dry aged unpackaged. This novel method of dry aging beef in a vacuum bag can increase yields, decrease microbial contamination, and provide processors greater flexibility of facility use, all of which would positively impact processors' profits.
Keywords: Cattlemen& #x27; s Day; 2006; Kansas Agricultural Experiment Station contribution; no. 06-205-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 959; Beef; Dry age; Vacuum packaging